Two new species of Clavellotis (Copepoda: Lernaeopodidae) with an approach to the phylogeny of the genus and its relationships inside the Clavella-Branch - Romero, Raul Castro; Montes, Martin M.; Ӧktener, Ahmet; Shimabukuro, Marina Ibañez; Theiller, Mariela; Campos, Leonardo (Zootaxa, 2025)
The identity of Clavellotis specimens parasitizing Chilean fishes has been determined using integrative taxonomy. Clavellotis dubius sp. nov., parasitic on Chromis crusma, can be distinguished from other species in the genus by a combination of characters, particularly the projection at the base of the cephalothorax, which shows variation related to the original aliform projection in Clavellotis. Additionally, its trunk is more elongated compared to the suborbicular trunk typical of other species. The male morphology aligns with the typical characteristics of the genus. The COI mtDNA genetic divergence between C. dubius sp. nov. and other Clavellotis ranges from 11.54% to 14.57%. Clavellotis girellae sp. nov., parasitic on Girella laevifrons, is morphologically similar to Clavellotis dilatata. However, males exhibit a unique dorsal projection shared only with Clavellotis sebastidis. The COI mtDNA genetic divergence for C. girellae sp. nov. ranges from 5.29% (with C. dilatata) to 12.94% (with C. sebastidis). With the addition of C. dubius and C. girellae, the number of Clavellotis species reported from Chilean fauna in the South Pacific increases to three, and the total number of species in the genus raises to 13. A phylogenetic analysis of Clavellotis is presented, including species from the South Pacific (C. dilatata, C. dubius sp. nov. and C. girellae sp. nov.), from South Atlantic (C. sebastidis) and Turkish Sea (Clavellotis fallax, Clavellotis strumosa, Clavellotis pagri and Clavellotis sargi). The analysis confirms the monophyly of Clavellotis, with C. sargi appearing as the most basal of the species within the genus. Additionally, the relationships of Clavellotis with other genera in the Clavella branch Alella, Clavella, Clavellisa Maxiclavella and Praeclavella—are also discussed.